The rise of multidrug resistant Salmonella isolates in healthy chickens in Brazil by successful establishment of plasmid IncHI2A carrying several antibiotic resistance genes - Penha Filho, Rafael Antonio Casarin [UNESP]; Ferreira, Joseane Cristina; Galetti, Renata; Kanashiro, Ana Maria Iba; Berchieri, Angelo [UNESP]; da Costa Darini, Ana Lúcia (Springer Nature, 2023)
Salmonella spp. is an important global issue in food-producing animals. The present study evaluated antimicrobial resistance and virulence profiles in Salmonella spp. isolates from chickens in Brazil. Identification of serotypes, virulence and antimicrobial resistance genes, and plasmid profiles were performed. Three different serovars were found, S. Schwarzengrund, S. Newport and S. Kentucky. All isolates were considered Multidrug- resistance (MDR). Among the 32 Salmonella spp. isolates analysed, 29 isolates carried blaCTX-M-2 gene and showed the insertion sequence ISCR1 and a class 1 integron structure upstream from blaCTX-M-2. This gene was harboured in large IncHI2A plasmids with approximately 280kb. Furthermore, 30 isolates harboured tetA and tetB genes and 25 also harboured qnrB. The virulence genes invA, misL, orfL, spiC and pipD were detected in all isolates. The study shows a high prevalence of MDR Salmonella isolates disseminated in poultry farms. The association of the replicon IncHI2A with the resistance genes found, elevate the risk of foodborne disease outbreaks.
Keywords: Brazil; ESBL; food-producing animals; poultry